ANALISIS DAN PERANCANGAN BASIS DATA SISTEM INFORMASI AKADEMIK PONDOK PESANTREN AL-QUR'AN ASSA'ADIYAH - Habibatul Adawiyah, (2022)
Academic information system is one of the facilities needed in the education system in Islamic boarding schools. Academic information system is a system designed to manage academic data of an agency engaged in education, one of which is in Islamic boarding schools. This study focuses on designing a database of academic information systems at the Al-Qur'an Islamic boarding school Assa'adiyah, which aims to produce an integrated database system design, facilitate the archiving of documents that are organized and recorded in the database, and can facilitate the search for academic data. from the Al-Qur'an Islamic Boarding School Assa'adiyah. This research using the method of DBLC (Database Development Life Cycle) which is the flow of the database design process where the database will continue to rotate or return to the starting point in updating according to the developments made. This research is expected to produce an Academic information system database design that can be implemented as a basic component in making the academic system of the Al-Qur'an Assa'adiyah Islamic boarding school in the future, as well as produce scientific writings in the form of national journals or proceedings that can be useful for anyone who need.